Int J Account Res 2019
DOI: 10.35248/2472-114x.19.7.197
|View full text |Cite
|
Sign up to set email alerts
|

Earnings Persistence and Firm Performance: Implications of Analysts? Accurate Forecast Ability from the Emerging Market of Nigeria

Abstract: This paper empirically examined the potency and value relevance of earnings persistence (EPERS) and its effect on firm performance and the implications of the analysts' accurate forecast ability from the emerging market of Nigeria. The study adopted the expo facto research design and sampled 51 companies listed on the Nigerian Stock Exchange using stratified random sampling techniques from all the sectors from the 2000-2016 periods. Descriptive and Panel data regression statistics were employed in the analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
0
16
2
1
Order By: Relevance
“…They found that operating performance is positively affected by earnings quality, and negatively affected by real earnings management. Dang et al (2020), Aguguom et al (2019) and Aguguom and Salawu (2018) documented that earnings quality is highly positively associated with companies' book value, and this refers to the relevance of information disclosure which enhances earnings quality, as well as credibility of reported book value. Chan et al (2006) discussed that stock returns are positively and negatively affected by earnings quality and earnings management, respectively.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…They found that operating performance is positively affected by earnings quality, and negatively affected by real earnings management. Dang et al (2020), Aguguom et al (2019) and Aguguom and Salawu (2018) documented that earnings quality is highly positively associated with companies' book value, and this refers to the relevance of information disclosure which enhances earnings quality, as well as credibility of reported book value. Chan et al (2006) discussed that stock returns are positively and negatively affected by earnings quality and earnings management, respectively.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…Investors are motivated by persistent earnings as a property of earnings quality. Aguguom, Dada, and Nwaobia (2019) posit that earnings persistence reflects managerial competence and ethical practices as an incentive to potential investors. Earnings persistence has a close relationship with firm value and economic wealth maximization for the shareholders.…”
Section: Conceptual Reviewmentioning
confidence: 99%
“…According to Canina and Potter (2019), earnings predictability considers the ability of earnings to predict themselves. Furthermore, earnings predictability is a desirable earnings attribute that enhances the forecast ability of analysts and investors (Aguguom et al, 2019;Festus, Rufus, & Janet, 2020). Earnings predictability is also a desirable property of earnings quality as it creates the impression of sustainable earnings based on the time-series properties of persistent earnings over the years.…”
Section: Conceptual Reviewmentioning
confidence: 99%
“…Cheng, 2005). Penelitian yang dilakukan oleh (Dawar, 2014) dan Aguguom et al (2019) dengan menguji hubungan antara earnings persistence dan harga saham pada pasar yang sedang berkembang terhadap future earnings response coefficient (FERC) menunjukkan bahwa earnings persistence berpengaruh positif terhadap FERC. Sejalan dengan penelitian yang dilakukan oleh Jang, et al (2007) yang juga menunjukkan bahwa earnings persistence berpengaruh positif terhadap FERC, yang berarti bahwa semakin tinggi earnings persistence yang dihasilkan perusahaan, maka kualitas laba perusahaan menjadi semakin tinggi juga.…”
Section: Pengembangan Hipotesis Pengaruh Earning Persistence Terhadap Future Earnings Response Coefficient (Ferc)unclassified